2014
DOI: 10.1007/s00520-014-2295-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient navigation moderates emotion and information demands of cancer treatment: a qualitative analysis

Abstract: Purpose Patient navigation is increasingly employed to guide patients through cancer treatment. We assessed the elements of navigation that promoted patients’ involvement in treatment among patients with breast and colorectal cancer that participated in a navigation study. Methods We conducted qualitative analysis of 28 audiotaped and transcribed semi-structured interviews of navigated and un-navigated cancer patients. Results Themes included feeling emotionally and cognitively overwhelmed and desire for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
7
12
0
Order By: Relevance
“…Preparation for medical appointments, which sometimes included "rehearsals" with the navigator, was perceived as helpful to patients. This result is consistent with several previous studies that showed a positive relationship between navigational services and communication between the patient and the medical team (11,26,27) . Our results also con rm those of other authors that communication support is a navigational service appreciated by patients (11,26,27) .…”
Section: Discussionsupporting
confidence: 93%
“…Preparation for medical appointments, which sometimes included "rehearsals" with the navigator, was perceived as helpful to patients. This result is consistent with several previous studies that showed a positive relationship between navigational services and communication between the patient and the medical team (11,26,27) . Our results also con rm those of other authors that communication support is a navigational service appreciated by patients (11,26,27) .…”
Section: Discussionsupporting
confidence: 93%
“…Similar to other research [18, 21], navigators in this study reported that financial burdens, work leave, insurance, and work-cancer fit were common concerns among their patients, with more nuanced findings highlighting the significant monetary burden cancer and its treatment places on patients [17]. Feedback from the navigators indicated a complex interplay of employment challenges that threaten the financial and overall wellbeing of patients.…”
Section: Discussionsupporting
confidence: 78%
“…Prior studies of care navigation in other diseases suggest ways that navigation programs have improved clinical health outcomes through decreased hospital readmissions among high-risk older adults in safety net settings, improved survival, and have addressed health disparities [1,10,33,34]. Many of these studies highlight the experience of navigation from the patient's perspective and focus primarily on the relationship between navigator and patient [35][36][37].…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%